A Highly Polymorphic Receptor Governs Many Distinct Self-Recognition Types within the Myxococcales Order - Pengbo Cao (American Society for Microbiology, 2019)
ABSTRACT Self-recognition underlies sociality in many group-living organisms. In bacteria, cells use various strategies to recognize kin to form social groups and, in some cases, to transition into multicellular life. One strategy relies on a single genetic locus that encodes a variable phenotypic tag (“greenbeard”) for recognizing other tag bearers. Previously, we discovered a polymorphic cell surface receptor called TraA that directs self-identification through homotypic interactions in the social bacterium Myxococcus xanthus. Recognition by TraA leads to cellular resource sharing in a process called outer membrane exchange (OME). A second gene in the traA operon, traB, is also required for OME but is not involved in recognition. Our prior studies of TraA identified only six recognition groups among closely related M. xanthus isolates. Here we hypothesize that the number of traA polymorphisms and, consequently, the diversity of recognition in wild isolates are much greater. To test this hypothesis, we expand the scope of TraA characterization to the order Myxococcales. From genomic sequences within the three suborders of Myxococcales, we identified 90 traA orthologs. Sequence analyses and functional characterization of traAB loci suggest that OME is well maintained among diverse myxobacterial taxonomic groups. Importantly, TraA orthologs are highly polymorphic within their variable domain, the region that confers selectivity in self-recognition. We experimentally defined 10 distinct recognition groups and, based on phylogenetic and experimental analyses, predicted >60 recognition groups among the 90 traA alleles. Taken together, our findings revealed a widespread greenbeard locus that mediates the diversity of self-recognition across the order Myxococcales. IMPORTANCE Many biological species distinguish self from nonself by using different mechanisms. Higher animals recognize close kin via complex processes that often involve the five senses, cognition, and learning, whereas some microbes achieve self-recognition simply through the activity of a single genetic locus. Here we describe a single locus, traA, in myxobacteria that governs cell-cell recognition within natural populations. We found that traA is widespread across the order Myxococcales. TraA is highly polymorphic among diverse myxobacterial isolates, and such polymorphisms determine selectivity in self-recognition. Through bioinformatic and experimental analyses, we showed that traA governs many distinct recognition groups within Myxococcales. This report provides an example in which a single locus influences social recognition across a wide phylogenetic range of natural populations.